Design of an Affordable Automated Injection Moulding Machine - Eddie, Sandra; Abakah-Paintsil, Kobina; Offei Ayisi, Nathan (MSD Institute, 2025)
Existing small-scale industries that use injection moulding machines employ manual machine operations. These manual operations result in fatigue and burns as the operators get into direct contact with the moulded part when ejecting it. Also, existing automated injection moulding machines are expensive. Hence, this work addresses the issues associated with the cost and the manual operation by employing a servo-electric hydraulic actuator to achieve the plunger mechanism, eliminating the fatigue involved with manually pushing the plunger. The ejection mechanism is performed automatically using NEMA 17 stepper motor, which moves half of the mould to eject the part. With temperature ranges up to 700 °C for the 27/5 cm mica heating bands and -200 °C to 1260 °C for the K-Type thermocouple used, all the recyclable types of plastics can be used as the raw materials for the injection process. The results obtained from the simulations using Proteus 8.13 show that the designed system can effectively and successfully improve the productivity and working conditions of operators. Cost analysis performed on the developed system showed that it was relatively cheaper with an estimated total cost of GH¢ 17,103.77 (USD 1,993.45).